Investigation of Cadmium, Lead, and Mercury Levels in the Urine of Renal Stone Patients in Najaf Governorate of Iraq - Mohammed, Kawther Hussein; Hady, Heiyam Najy; Mraity, Hussien Abid Ali Bakir (Iraqi Journal of Science, 2026)
This study aims to determine the levels of cadmium (Cd), lead (Pb), and mercury (Hg) in the urine of renal stone patients and a healthy control group in the Najaf Governorate of Iraq using Atomic absorption spectrometry (AAS). The study included 20 renal stone patients and 20 healthy individuals as a control group. Both groups consisted of 10 women and 10 men. The results demonstrated that there was a significant difference (p <0.001) in the levels of (Cd, Pb, and Hg) in the urine of renal stone patients compared with the control group. Also, there was a statistically significant difference in Pb and Hg levels in the urine of females, which were seen to be more than that of males (p < 0.005). The difference was statistically significant p < 0.001, in the Receiver Operator Characteristic (ROC) curve analysis for levels of Cd, Pb, and Hg in urine, which showed a high area under the ROC curve (AUC) values of 0.978,1.000, 1.000, respectively. The high levels of cadmium, lead, and mercury in urine may affect kidney function and impose certain toxic issues for the kidney and can be considered as a potential factor for the occurrence of renal stones.